An International survey on living kidney donation and transplant practices during the COVID‐19 pandemic. Issue 2 (19th December 2020) - Salvalaggio, Paolo R.; Ferreira, Gustavo F.; Caliskan, Yasar; Vest, Luke S.; Schnitzler, Mark A.; de Sandes‐Freitas, Taina V.; Moura, Lucio R.; Lam, Ngan N.; Maldonado, Rafael A.; Loupy, Alexandre; Axelrod, David A.; Lentine, Krista L.
Abstract: The scope of the impact of the Coronaviru s disease 19 (COVID‐19) pandemic on living donor kidney transplantation (LDKT) practices across the world is not well‐defined. We received survey responses from 204 transplant centers internationally from May to June 2020 regarding the impact of the COVID‐19 pandemic on LDKT practices. Respondents represented 16 countries on five continents. Overall, 75% of responding centers reported that LDKT surgery was on hold (from 67% of North American centers to 91% of European centers). The majority (59%) of centers reported that new donor evaluations were stopped (from 46% of North American centers to 86% of European centers), with additional 23% of centers reporting important decrease in evaluations. Only 10% of centers reported slight variations on their evaluations. For the centers that continued donor evaluations, 40% performed in‐person visits, 68% by video, and 42% by telephone. Center concerns for donor (82%) and recipient (76%) safety were the leading barriers to LDKT during the pandemic, followed by patients concerns (48%), and government restrictions (46%). European centers reported more barriers related to staff limitations while North and Latin American centers were more concerned with testing capacity and insufficient resources including protective equipment. As LDKT resumes, 96% of the programs intend to screen donor and recipient pairs for coronavirus infection, most of them with polymerase chain reaction testing of nasopharyngeal swab samples. The COVID‐19 pandemic has had broad impact on all aspects of LDKT practice. Ongoing research and consensus‐building are needed to guide safe reopening of LDKT programs.